Geochemical Specifics and Patterns of the Distribution of Heavy Metals in the Opuksky Sanctuary, Republic of Crimea. Issue 5 (March 2021) - Zelenkovskiy, P; Solovieva, E; Dubrova, S; Sikorsky, I; Evenkova, T
Abstract: This paper evaluates the ecological and geochemical status of soils in the Opuksky Sanctuary, Republic of Crimea, Russia. The Sanctuary has been a nature reserve since the mid- 20th century. It is located on the Black Sea coast of the Kerch Peninsula, the Republic of Crimea. This is an integrated sanctuary established to preserve the unique steppe ecosystems associated with the limestone massif of Mount Opuk and Lake Koyashskoye, a salt lake which has a number of one-of-a-kind nature sites within a small area and features several rare species. The water area of the Sanctuary is a wetland protected international under the Ramsar Convention. The increasing anthropogenic pressure arising from agricultural and industrial development of the Crimean Peninsula, as well as the increasing tourist flow that must be controlled is what makes monitoring the area critical. Soil is the most sensitive natural environmental component to anthropogenic effects; as such, it was monitored over three years from 2017 through 2019 as part of St. Petersburg State University, Department of Environmental Geology's student internship co-organized with the administration of the Sanctuary. This effort produced a map of heavy metals in the local soils. The authors described the patterns in pollutant migration; they also prove why the soil was vulnerable to contamination. The research effort was the first to collect data on the background presence of trace elements in the soils of potentially uncontaminated areas; this data could be of use for engineering and environmental surveying across the region. Such data is becoming relevant and essential as the Republic of Crimea's heavy industry and agriculture are rising.